Resolving the mechanisms of hygroscopic growth and cloud condensation nuclei activity for organic particulate matter. Issue 1 (December 2018) - Liu, Pengfei; Song, Mijung; Zhao, Tianning; Gunthe, Sachin; Ham, Suhan; He, Yipeng; Qin, Yi; Gong, Zhaoheng; Amorim, Juliana; Bertram, Allan; Martin, Scot
Abstract Hygroscopic growth and cloud condensation nuclei activation are key processes for accurately modeling the climate impacts of organic particulate matter. Nevertheless, the microphysical mechanisms of these processes remain unresolved. Here we report complex thermodynamic behaviors, including humidity-dependent hygroscopicity, diameter-dependent cloud condensation nuclei activity, and liquid–liquid phase separation in the laboratory for biogenically derived secondary organic material representative of similar atmospheric organic particulate matter. These behaviors can be explained by the non-ideal mixing of water with hydrophobic and hydrophilic organic components. The non-ideality-driven liquid–liquid phase separation further enhances water uptake and induces lowered surface tension at high relative humidity, which result in a lower barrier to cloud condensation nuclei activation. By comparison, secondary organic material representing anthropogenic sources does not exhibit complex thermodynamic behavior. The combined results highlight the importance of detailed thermodynamic representations of the hygroscopicity and cloud condensation nuclei activity in models of the Earth's climate system. The interactions between organic particulate matter and water vapour affect climate predictions, yet the mechanisms of these interactions remain unresolved. Here, the authors propose a phase separation mechanism that reconciles the observed hygroscopicity and cloud condensation nuclei activity.